Non-protein amino acids in Australian acacia seed: Implications for food security and recommended processing methods to reduce djenkolic acid. (15th July 2015) - Boughton, Berin A.; Reddy, Priyanka; Boland, Martin P.; Roessner, Ute; Yates, Peter
Highlights: Australian acacia has potential to contribute to the agriculture of semi-arid Africa. Five Australian acacia varieties were screened for toxic non-protein amino acids. Australian acacia found to contain elevated levels of nephrotoxic djenkolic acid. The implications of acacia use as a famine food explored. Djenkolic acid content reduced to safe levels by roasting for between 8 and 10 min. Abstract: Seed of Australian acacia species, Acacia colei, Acacia elecantha, Acacia torulosa, Acacia turmida and Acacia saligna, were analysed for the presence of toxic non-protein amino acids and the levels of essential amino acids. Amines were derivatised with 6-aminoquinolyl- N -hydroxysuccinimidyl carbamate before analysis using liquid chromatography electrospray ionisation triple quadrupole mass spectrometry (LC-ESI-QQQ-MS). Multiple reaction monitoring (MRM) with optimised transitions and collision energies for each analyte were employed. The known nephrotoxic compound djenkolic acid was found to be present at elevated levels in all species tested. The lowest levels were in A. colei (0.49% w/w) and the highest in A. saligna (1.85% w/w). Observed levels of djenkolic acid are comparable to measured and reported levels found in the djenkol bean. Subsequent testing of seed processing methods showed djenkolic acid levels can be significantly reduced by over 90% by dry roasting at 180 °C rendering the seed safe for human consumption.